A review study on the using of diethyl ether in diesel engines: effects on smoke and PM emissions - İsmet Sezer (MANAS: Journal of Engineering)
This study wascompiled from the results of various researches performed on using diethylether as a fuel or fuel additive in diesel engines. Three different techniquesare used the reduction of the harmful exhaust emissions of diesel engines. Thefirst technique for the reduction of harmful emissions is improved thecombustion by modification of engine design and fuel injection system, but thisprocess is expensive and time consuming. The second technique is the using variousexhaust gas devices like catalytic converter and diesel particulate filter.However, the use of these devices affects negatively diesel engine performance.The final technique to reduce emissions and also improve diesel engineperformance is the use of various alternative fuels or fuel additives. Themajor pollutants of diesel engines are oxide of nitrogen (NOx) and smoke orparticulate matter (PM). It is very difficult to reduce NOx and PMsimultaneously in practice. The most researches declare that the best way toreduce is the use of various alternative fuels i.e. natural gas, biogas,biodiesel or using the additives with alternative fuels or conventional dieselfuel. Therefore, it is very important that the results of various studies onalternative fuels or fuel additives are evaluated together to practiceapplications. Especially, this study focus on the use diethyl ether in dieselengines as fuel or fuel additive in various diesel engine fuels. This reviewstudy investigates the effects of diethyl ether addition on the smoke and PMemissions.